Peningkatan Minat Bakat Robot pada Siswa SMP/MTs di Kelurahan Tanjung Harapan, Samboja Timur, Kutai Kartanegara - Andi Asni B.; Aswadul Fitri Saiful Rahman; Anwar Fattah; Diah Patriana Setianingsih; Khairunnisa Nurhandayani; Mayda Waruni Kasrani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Technology is always developing every year. In the technological development of Industrial Revolution 4.0, human work is almost dominated by automation systems, artificial intelligence, and the Internet of Things (IoT). The basis for the application of these three types of technology is robot technology that can move in simple or complex ways. The results Forum Pendidikan Tinggi Teknik Elektro Indonesia (FORTEI) meeting showed a decrease in interest in new engineering students in 2020 by 2.3%. This has an impact on human resources who do not understand technology which is constantly changing so that it can affect the use of domestic technologyThe method of delivering material, discussion and direct testing of tools is used to increase demand related to electricity and robots in the form of training activities. This training is targeted at SMP/MTs students because at this level students develop their knowledge and curiosity. After the training was carried out, there was an increase in students' understanding and interest by 45%.